LEARNING MODEL WITH STEAM APPROACH ASSISTED LKPD AND QUIZIZZ TO IMPROVE STUDENT PROBLEM SOLVING ABILITY - Rahmawati Rahmawati; Desi Andriani; Rian Amirul; Rahmad Halim (Universitas Negeri Makassar, 2023)
The purpose of this study was to determine the increase in students' mathematical problem solving abilities which were taught with STEAM model lessons assisted by LKPD and Quizizz. STEM education is defined as an integrated learning approach from the concepts of science, technology, engineering and mathematics. The subjects used were class X students and samples taken in class X1 and X2 were 50 students of MA. Al-Fatah Palembang for the 2020-2021 academic year. Quasi- experimental method used in this study. STEAM model lessons assisted by LKPD and Quizizz show a higher KPMM than students who receive conventional learning, it can be seen from the count > t table, namely 9.78 > 1.71 t-test formula. Assuming that there are differences in the treatment of the control class in class X MA.Al-Fatah Palembang students, it can be concluded that the average test scores using STEAM models assisted by LKPD and Quizizz are better than conventional learning